Tinjauan Pustaka: Pengaruh Vitamin C, Vitamin D, dan Zinc Terhadap COVID-19 - Eva Hiikmatul Damayanti; Catarina Budyono (Faculty of Medicine Universitas Mataram, 2022)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is an emerging, highly contagious and pathogenic coronavirus. To date, there is no definitive therapy for SARS-Cov-2 infection known as COVID-19. Supportive therapy that can be done is the provision of vitamin and mineral supplementation by consuming vitamin C, vitamin D, and zinc. Several studies have shown that oral and intravenous administration of vitamin C can reduce the increased risk of complications, reduce severity, improve symptoms and improve prognosis with COVID-19. Zinc might reduce the risk of SARS-CoV-2 infection and shorten the duration and severity of illness.